2001
DOI: 10.1080/20702620.2001.10434148
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Eucalyptus species to fertilizer applications made at planting on granitic parent materials in the Mpumalanga and Northern Provinces of South Africa

Abstract: SYNOPSISEarly research trials in South Africa have shown that Eucalyptus species generally respond positively to the addition of nutrients at planting. However, as most of these research trials were located in KwaZuluNatal, it was important to investigate the nature of the response in other afforested regions of the country where this genus is planted. Consequently, a number offertilizer trials were established in the late 1980's and early 90's in Mpumalanga and the Northern Province to investigate the nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…We found that the benefit of NPK fertilization decreased with time. This phenomenon has been noticed in previous studies and reviews [14,74,75] and several factors are believed to explain this trend. During the initial establishment phase, young seedlings generally do not have well developed root systems and providing easily accessible inorganic forms of nutrients can increase growth [18•, 74].…”
Section: Inorganic Npk Fertilizationsupporting
confidence: 75%
“…We found that the benefit of NPK fertilization decreased with time. This phenomenon has been noticed in previous studies and reviews [14,74,75] and several factors are believed to explain this trend. During the initial establishment phase, young seedlings generally do not have well developed root systems and providing easily accessible inorganic forms of nutrients can increase growth [18•, 74].…”
Section: Inorganic Npk Fertilizationsupporting
confidence: 75%
“…More specifically, during the last half century, there has been substantial experimentation with fertilizers at time of establishment, which covered a wide range of species, site types and establishment conditions. Summaries of results from these empirical fertilizer trials on hardwood plantations have been documented by Schö nau et al (1981), Schö nau (1983, Herbert andSchö nau (1989, 1990), Noble and Herbert (1991), Herbert (1996), Carlson et al (2001), du Toit et al (2001, du Toit (2002), du Toit and Oscroft (2003), and du Toit and Drew (2003). Fertilization at establishment has the potential to substantially boost the productivity of shortrotation hardwood crops.…”
Section: Effects Of Harvest Residue Management and Fertilization On Smentioning
confidence: 96%
“…Optimum applications usually fall in the range 0-30 g N tree À1 (rarely up to 50 g N tree À1 ); 10-20 g P tree À1 and 0-15 g K tree À1 , depending on soil type, site conditions and harvest residue management ( Table 2). Most of the documented responses show that an increase in timber volume on a mature (6-10 year old) eucalypt rotation can vary form 20 to 90 m 3 ha À1 with a concurrent increase in wood density of 15-30 kg m À3 (Schö nau, 1983;Herbert andSchö nau, 1989, 1990;Herbert, 1996;Carlson et al, 2001;du Toit et al, 2001;du Toit and Oscroft, 2003;du Toit and Drew, 2003). However, there are a number of examples of early hardwood experiments that did not respond significantly to fertilizer applications, where the experiments were abandoned without reporting the non-response in the formal literature.…”
Section: Effects Of Harvest Residue Management and Fertilization On Smentioning
confidence: 99%
“…addition of nutrients through natural processes such as mineral weathering, nitrogen (N) fixation and atmospheric deposition) are the basic components of the nutrients cycling process within the forest ecosystem (Smethurst 2010;Dovey et al 2011). Research has shown that most fertiliser applications in South African commercial forestry are localised on a per tree basis and done at time of establishment to promote root proliferation and stand uniformity (Schӧnau et al 1981;Carlson et al 2001;du Toit et al 2010). Current knowledge in the literature suggests that these fertiliser applications are imperative for (1) long-term nutritional sustainability of the commercial forest for optimal plantation productivity and (2) replenish the soil nutrient losses due to harvest and leaching to the deeper soil profile, drainage systems and groundwater (Grierson and Adams 1999).…”
mentioning
confidence: 99%